ANALISIS KEBUTUHAN AIR BERSIH DI KECAMATAN SELAT NASIK KABUPATEN BELITUNG PROVINSI BANGKA BELITUNG TAHUN 2017 - Ika Kusumawati (Journal of Environmental Engineering and Waste Management, 2018)
Kecamatan Selat Nasik is one of the subdistricts in Belitung Regency with limited avaliability of clean water. It is because the district located in the archipelago with limited clean water sources. The purpose of this study is to determine the potential of clean water. The analysis of this study are: clean water analysis, population growth analysis, and water availability analysis. The final result shows availability of clean water both 466.366 liter per person per day (in 2018) and 519.611 liter per person per day (in 2023). While the necessity of clean water required both 586.260 liter per person per day (in 2018) and 556.470 liter per person per day (in 2023). In other words, the needs of clean water in Kecamatan Nasik until 2023 can not been able to cover necessity of clean water population yet.